The usefulness of music as a tool of teaching Islamic education: Teachers’ perspective - Ramdane, Tahraoui; Souad, Merah; Marusin, Ratinah; Md. Sidek, Suzana Suhailawaty (IIUM Press, International Islamic University Malaysia, 2018)
This paper addresses the use of songs by Malaysian Islamic Education teachers in their classrooms in order to help their students understand the Islamic education topics in a more effective and enjoyable manner. Furthermore, this paper provides an insight about the role of teachers in implementing innovative approaches via songs, which brings to the forefront an awareness about effective teaching strategies, not only for in-service teachers but also for those who are responsible for educating and training Islamic Education teachers in the future. This study employs a quantitative cross-sectional research design, utilizing surveys and questionnaires. The population of this study comprised Islamic Education teachers in primary schools in the Kuala Selangor District, in the State of Selangor. The sampling technique adopted by the researcher was purposive because data based on the knowledge and experience of teachers were the main aim of the research. The results of this study revealed that not only the students benefited from the use of songs but also teachers. The impact comprised areas which teachers of Islamic education usually receive a lot of criticism, such as creativity, thinking and communication skills, emotions, motivation and spiritual development.